Classification Of Interest In Sports Using The Naive Bayes Classifier Method - Lumbantobing, Martin; Novita, Nanda (Universitas Medan Area, 2025)
Interest in sports must be done from an early age and requires the right method to achieve the desired results, namely by using the Naive Bayes method. The purpose of this study was to explore the sports interests of students of SDN 3 Tarutung with the Naive Bayes method. The subjects of this study were students in grades 4, 5, and 6 of SDN Jenggolo Tuban who liked sports using data collection methods, namely the Naive Bayes method, Observation, Interviews and practical sports tests based on sport search, namely Height (TB), Sitting height (TD), Weight (BB), Arm span (RL), Tennis ball throw and catch (LTBT), Basketball throw (LBB), Vertical jump (LT), Agility run (LK), 60 meter sprint (L60M), and multi-stage run (MFT). The Naive Bayes modeling system is carried out in two phases, namely training data and testing data. The results of the study obtained were the results of the classification of each student who was talented in sports (football, volleyball, badminton, sprinting, swimming) or not talented in sports (football, volleyball, badminton, sprinting, and swimming). The results of the testing data showed that 7 students were talented in football, 2 students were talented in volleyball, 1 student was talented in badminton, 5 students were talented in sprinting, and 3 students were talented in swimming.